PERAN MIKORIZA PADA Acacia auriculiformis YANG DITUMBUHKAN PADA TANAH SALIN - , Miranda H.Hadijah,S.Hut., Dr. Ir. Eny Faridah, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Saline habitats are characterized by an excess of inorganic salts and mainly occurs in arid and semi-arid regions. Accumulation of salts in the topsoil is usually resulted by evapotranspiration leads the rise of ground water containing salt. Biological processes such as application of mycorrhiza to alleviate salt stress and the use of tree species tolerant to the salt is a better choice. Acacia auriculiformis is included in the fast growing species and pioneer reclamation plant because it can grow even in very poor conditions in the tropics. The use of mycorrhizal fungi as a biological agent in agriculture and forestry can improve growth, productivity and quality of crops without damaging the soil ecosystem. In addition, application of mycorrhizal fungi can help degraded land rehabilitation and improve crop productivity on marginal lands including saline soils. The research objectives were to study the influence of saline condition on seedling growth of A. auriculiformis, knowing mycorrhizae roles on A. auriculiformis seedling in facing salinity stress, and knowing the level of salinity that can be tolerated by A. auriculiformis seedling inocucated by mycorrhizae. The research was conducted in January-November 2011 using the RCBD (Randomized Complete Block Design) consisting of two factors. The first factor was endomikoriza fungi inoculation (I) consist of two levels and the second factor was the salinity (S) consist of five levels. Measured and observed parameters were seedling height, stem diameter, leaf number, total wet weight, root infection, growing media analysis and leaf tissue analysis. The results showed that the inoculation of the endomikoriza significantly influenced height increment, total wet weight and seedling root infection of A. auriculiformis. Salinity did not significantly affect all measured parameters, while the interaction between endomikoriza fungi inoculation and salinity was significant only in leaf increment. In the infected root of A. auriculiformis seedling, there were internal hyphae, vesicles, or both of them while arbuscula was not found. Seedlings inoculated by endomikorizal fungi and given salinity stress have higher P and N content than non-inoculated seedlings on the same level of salinity, but at the higher concentration P and N content started to decrease. K content was lower in the inoculated seedling than the non-inoculated on the same level of salinity, as well as on the seedlings were not given the salinity stress. The high of soil salinity in the growing media has a positive effect on endomikoriza fungi infection of A. auriculiformis seedling roots. Na uptake in noninoculated tends to be higher than the inoculated seedlings. It showed that the endomikorizal fungi help A. auriculiformis seedling to retain Na in the roots are not transported to the shoots.